If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 3) * 2 + -81 = 0 Reorder the terms: (3 + y) * 2 + -81 = 0 Reorder the terms for easier multiplication: 2(3 + y) + -81 = 0 (3 * 2 + y * 2) + -81 = 0 (6 + 2y) + -81 = 0 Reorder the terms: 6 + -81 + 2y = 0 Combine like terms: 6 + -81 = -75 -75 + 2y = 0 Solving -75 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '75' to each side of the equation. -75 + 75 + 2y = 0 + 75 Combine like terms: -75 + 75 = 0 0 + 2y = 0 + 75 2y = 0 + 75 Combine like terms: 0 + 75 = 75 2y = 75 Divide each side by '2'. y = 37.5 Simplifying y = 37.5
| m-33=-7(-11-8m) | | 18x-6=13x-11 | | 1-3/2x=7/4 | | Sqrt(9x^2)=y | | Sqrt(9x^2)=0 | | 3.4=0.4x | | 7x+2-8x=0 | | (3x-4)(6x-2)= | | -7x+49=7x-49 | | 3x+8-x=29 | | 1/2+1/5=56 | | (-4m+6)(3m+2)= | | 2w^2+w-55=0 | | 2p^3-3p^2-98p+147=0 | | 1/6(6x-5)=7/6-5/6 | | 2Y+20=46 | | 5ab+12b= | | 2p^3-3p^2-98p+37=0 | | 4x^2-9x-22=0 | | (5w+2)(8w+5)= | | 0=-32+16t^2-16t | | 8x+12y= | | 5x-7=40x+7 | | 44-12x=-8(x-7) | | 7x+7=5x+1 | | 2x-y=-18 | | 35x^3+21x+14^4/7x | | x/x-6-4=6/x-6 | | -3x^2-4x+224=0 | | 5z-11-2z+5=0 | | x/8-3=-5 | | X^2+3x-255=3x |